The Role of Pancasila Education Teachers in: Implementing the Independent Pancasila Student Profile for Children with Special Needs at Muhammadiyah 2 Middle School, Ponorogo - Ambiro Puji Asmaroini; Hadi Cahyono; Dwi Setyani (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
This study applies a qualitative approach to examine the role of Pancasila education teachers in implementing the Pancasila student independence profile for children with special needs at SMP Muhammadiyah 2, Ponorogo, a technique for collecting data covering observation, interviews, and recording. Observations are made to understand the direct learning process and interaction between the Teacher And students. We interview the head of the school, the leader of the curriculum, and the Teacher Pancasila Education to gather information, perspectives, and obstacles faced in carrying out learning. Documentation is used to obtain additional data in the form of supporting documents. This study's data analysis process includes data reduction, presentation, and conclusion. Data reduction involves filtering and summarizing important information from the raw data obtained. The data is presented as a narrative description to describe the phenomenon being studied in depth. Conclusions are drawn systematically based on patterns and findings identified during analysis, which answer the formulation of the problem. Research results show that Teacher Pancasila education plays a strategic role as a source of learning, facilitator, manager, demonstrator, mentor, and evaluator in supporting the development of independent children with special needs. Teachers must also understand biological, psychological, and student cultures to create meaningful experiences. Factors supporting the success of implementation include other support policies, an inclusive environment, friendly study involvement, an active person, old age, dedication, and the competence of teachers. However, this implementation also faces challenges like limited facilities, a lack of understanding of teachers about learning inclusivity, and public awareness about the importance of inclusive education